Cognitive Assessments Used in Occupational Therapy Practice: A Global Perspective. (26th August 2020) - Manee, Fahad S.; Nadar, Mohammed Shaban; Alotaibi, Naser M.; Rassafiani, Mehdi
Abstract : This exploratory study was aimed at evaluating the current status of global occupational therapy practice on the use of assessments for clients with cognitive impairments and providing recommendations for ongoing evidence. We targeted international occupational therapy clinicians working with clients experiencing neurocognitive impairments. 323 occupational therapists from a wide range of clinical practice areas participated in the study. A large number of therapists used noncognitive specific assessments with a focus on functional approaches. The most commonly used standardized assessments were the COPM (56.7%), followed by MMSE (54.2%) and MoCA (45.5%), while the nonstandardized assessments were clinical observation (38.4%) and generic ADL assessment (34.1%). The use of main assessments was significantly different across world regions (p < 0.05 ), as were the reasons for choosing them (p < 0.05 ). The occupational therapists' use of assessment tools with clients suffering from neurocognitive impairments is inconsistent across the globe. The identification of international best practices for selecting and implementing proper outcome measures is warranted. It is essential to promote the development of an occupational therapy initiative to support the use of appropriate assessments at the international levels to facilitate consistent best practice.